The Notary Role / PPAT in Improving Legal Awareness Society to Perform Registration Rights to Land Based on Government Regulation No. 24 of 1997 on Land Registration - Widyawati Widyawati; Tafta Aji Prihandono; Widhi Handoko (Jurnal Akta, 2018)
The purpose of this study: 1) to analyze the Notary role / PPAT in raising legal awareness in the registration of land rights in Pati Regency, according to Government Regulation No. 24 of 1997 on Land Registration. 2) to analyze the obstacles and solutions role of the Notary / PPAT in increasing of public awareness for the registration of land rights in Pati regency. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analytical method.Based on the results of data analysis concluded that: the role of the Notary / PPAT in increasing of public awareness for the registration of land rights in Pati Regency, according to Regulation No. 24 of 1997 on Land Registration can be said to have not been successful, due to the lack of socialization of Notary / PPAT up to the suburbs Pati city where people still common law. Barriers Notary / PPAT in increasing of public awareness for the registration of land rights in Pati regency namely external and internal factors. The solution Notaries should cooperate with other parties for the success of socialization, such as cooperation with the press.Keywords: Notary Role; Socialization; Legal Understanding.